2008
DOI: 10.1128/jcm.00757-08
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Perinatal Cytomegalovirus Infection and Sensorineural Hearing Loss in Belgian Infants by Measurement of Automated Auditory Brainstem Response

Abstract: Since auditory disability causes serious problems in the development of speech and in the total development of a child, it is crucial to diagnose possible hearing impairment as soon as possible after birth. This study evaluates the neonatal hearing screening program in Flanders, Belgium. The auditory ability of 118,438 babies was tested using the automated auditory brainstem response. We selected 194 babies with indicative hearing impairment and 332 matched controls to investigate the association between the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…Frequency of sensorineural hearing loss among congenitally infected children according to cytomegalovirus (CMV) viral load at birth. Each group of bars represents measurements from a single study (listed in Table A5 [102][103][104][105][106][107]). In one study, [104] viral load was measured in urine and blood, so two sets of bars are presented.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency of sensorineural hearing loss among congenitally infected children according to cytomegalovirus (CMV) viral load at birth. Each group of bars represents measurements from a single study (listed in Table A5 [102][103][104][105][106][107]). In one study, [104] viral load was measured in urine and blood, so two sets of bars are presented.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the previous report, our results also demonstrated that elevated IL-6 levels in UCB, reflecting an in utero initiation of the fetal response to perinatal events, were significantly associated with NHS test failure. Given that IL-6 is a well-known important mediator of host response to infection [ 22 ], which in turn is significantly involved in the pathogenesis of sensorineural hearing impairment [ 10 , 23 ], these observations are not unexpected and support the hypothesis that a systemic fetal inflammatory response may be detrimental to auditory function in preterm infants.…”
Section: Discussionmentioning
confidence: 86%
“…Among these studies, the frequency of SNHL in individuals with acquired CMV infection was slightly higher (19.78%) compared to the frequency of CMV infected individuals without SNHL (15.86%). However, given that only six studies could be selected for the metanalysis and the study of Verbeeck et al [ 25 ] contributed with 48% of the individuals, we cannot rule out a bias. Overall, according to the meta-analysis, CMV shows no association with SNHL, while the association with tinnitus has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The data were retrieved from each study and the following information was extracted: first author’s last name, year of publication, study design, population studied, case and control group definition, hearing results, method of ascertainment and determinant of viral-infection and relationship between acquired CMV infection and SNHL ( Table 1 ) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%